Circular ecosystem innovation: An initial set of principles. (20th April 2020) - Konietzko, Jan; Bocken, Nancy; Hultink, Erik Jan
Abstract: A circular economy maximizes the value of material resources and minimizes greenhouse gas emissions, resource use, waste and pollution. We will posit that circularity needs to be understood as a property of a system (e.g., the mobility system of a city), rather than a property of an individual product or service (e.g., a car or a car-sharing service). Hence, there is a need for more knowledge on how to innovate towards 'circular ecosystems'. This study proposes a set of principles for 'circular ecosystem innovation', based on: 1) a concise literature review to retrieve recommended principles on how to successfully innovate in ecosystems, 2) a mobility case of circular ecosystem innovation to investigate how relevant and useful these principles are for circular oriented innovation. The case data include 20 interviews, workshop data and internal background documents. The identified principles can be categorized in three groups: 1) collaboration (i.e., how firms can interact with other organizations in their ecosystem to innovate towards circularity), 2) experimentation (i.e., how firms can organize a structured trial-and-error process to implement greater circularity) and 3) platformization (i.e., how firms can organize social and economic interactions via online platforms to achieve greater circularity). Future research may focus on identifying opportunities and barriers to applying these principles in different contexts than in the one that is investigated in the present study. Highlights: We present literature and a case on 'circular ecosystem innovation'. Circularity is argued to be a property of a system, rather than a single product. Circular ecosystems widen the lens of product and business model innovation. We propose a set of recommended principles for circular ecosystem innovation. Principles can be grouped into experimentation, collaboration and platformization.